Slice, Then Stitch. (Communications of the ACM, 2009)
The article reports that researchers have developed computer software that enables large sets of data to be analyzed and visualized without the aid of supercomputers. A description is given of the manner in which the researcher's algorithm handles the data in order to manipulate the data into three dimensions.